Perbandingan Performa Juvenil teripang pasir, Holothuria scabra yang diberi pakan Ulva dan Sargassum. - Tomatala, Pitjont; Kalean, Soraya; Arianto, Dwi; Pattiwael, Steven (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
Sandfish (Holothuria scabra) are one of the economically important marine animals found in the coastal of the Kei Islands (Tual City and Southeast Maluku Regency). The large exploitation pressure caused the sandfish population in the Kei Islands to decline drastically. This problem can be overcome by farming activities (greeding, nursery and grow-out). Nursery is an important segment in the farming series because through nursery the seeds are prepared to a size that good for rearing in grow-out containers or restocking into nature. This research aims to see the effect of giving Sargasum sp and Ulva sp extracts on the growth and survival of sandfish juveniles. This research doing from August – September 2022 at the Tual Teripang Center, Ohoitel village, Tual City. Juvenile sandfish used as research objects size 3 – 6 mm and stocking density is 40 individu per container. The feed used as treatment was Ulva sp extract 50 g/container (treatment A) and Sargasum sp extract 50 g/container (treatment B). Feeding is done every day and water changes are 70-100% per day. The calculation of growth and survival rate is the variable that observed in this study. The average absolute growth in body length in treatment A was 0.69 mm and in treatment B was 1.72 mm. Through the T test on growth, it was obtained that Pvalue (0.0006) < α (0.05) which means that the two treatments had different effects on juvenile growth. For survival, the average percentage for Treatment A was 40% and Treatment B was 62.5%. Through the T test on survival, it was obtained that Pvalue (0.0048) < α (0.05) which means that the two treatments had different effects on the survival of juvenile sea cucumbers. It was concluded that treatment B was better for the growth of juvenile sandfish than treatment A.